Development of coconut shell-based microwave absorbers / Mohd Kamarulzamin Salleh - Salleh, Mohd Kamarulzamin (2015)
Magnetic materials are widely used as radar absorbing materials. However, they are heavy and their performance at microwave frequencies are limited. Coconut shell is a carbon-based material and offers alternative since it is lighter, thus opening the possibility of producing light-weight, broader bandwidth microwave absorbers. Coconut shell-based microwave absorbers are studied in thiswork. Activated carbon powder derived from coconut shells was mixed with Flaxane-80 to give 10%, 15%, 20%, 25% and 30% variation of carbon. The microwave properties of the samples investigated included the real and imaginary parts of the permittivity, and tan 8. The carbon content in the samples was varied to examine the microwave properties in the X-band using the microwave non-destructive testing (MNDT) technique. It was found that the permittivity (real and imaginary) and tan 8 increased for an increase in the carbon content. The relative permittivity of 30% carbon sample was found to be the highest with a value of 17. The sample also has the highest tan 8 of 0.14. The reflection properties of single layer and multi-layer microwave absorbers were studied using CST Microwave Studio simulation and MNDT measurements. For the single layer absorbers, the impact of permittivity, tan 8, thickness and carbon content on the reflection properties were examined. The coconut shells content and thicknesses were varied from 10% to 30% and 3.2 mm to 13.8 mm respectively. The absorber thickness controlled the resonant frequency whereby increasing the thickness caused the resonant frequency to decrease. Tan 8 influenced the level of reflected power in which the reflection was reduced for a higher tan 8. The permittivity and carbon content were found to control both the resonant frequency and the level of reflected power. For an increase in permittivity and carbon content, the resonant frequency shifted to a lower value. The sample with 7.5mm thickness made of 25% coconut shells showed the best performance with minimum reflection at 10.25 GHz with -17.5 dB reflection loss. For multi-layer absorbers, two, three and four-layer samples were modelled and fabricated. A binomial multi-section transformer was used to provide a smooth transition impedance between the layers. The top layer, which was the nearest layer to the air, utilised the lowest carbon content with the highest impedance while the bottom layer used the highest carbon content with the corresponding lowest impedance. Multi-layer absorbers offer a wider bandwidth compared to single layer absorbers. By adding more layers, the absorber bandwidth was extended and the amount of reflection reduced. All the fourlayer absorbers fabricated in this work showed excellent performance in absorbing microwave signals, exhibiting respectable wideband performance. The four-layer sample with combinations of 0%, 15%, 25% and 30% carbon shows the best performance with 21% bandwidth below -15 dB from 8.0 GHz to 9.9 GHz. This study shows that coconut shell is a promising material for developing microwave absorbers using local materials.